Enabling Self-Directed Academic and Personal Wellbeing Through Cognitive Education - Van Tonder, Gideon P.; Kloppers, Magdalena M.; Grosser, Mary M. (Frontiers in Psychology, 2022)
Background The international crisis of declining learner wellbeing exacerbated by the COVID-19 pandemic with its devastating effects on physical health and wellbeing, impels the prioritization of initiatives for specifically enabling academic and personal wellbeing among school learners to ensure autonomous functioning and flourishing in academic and daily life. Research emphasizes the role of self-directed action in fostering wellbeing. However, there is limited research evidence of how self-directed action among school learners could be advanced. Aim We explore the effectiveness of an intervention initiative that exposes teachers to foregrounding Cognitive Education – the explicit and purposeful teaching of thinking skills and dispositions to learners that would advance self-regulated action - to establish the latent potential of the intervention for assisting learners to develop self-regulating abilities that progressively inspires increased self-directed action. Method We illuminate the qualitative outcomes of an exploratory pilot study with a heterogeneous group of willing in-service teachers from two public primary schools (n = 12), one private primary school (n = 3), and one pre-school (n = 2) in South Africa who received exposure to an 80-h intervention that comprised seven study units. The article delineates the experiences of the teachers concerning their participation in the intervention as reflected in their written reflections, as well as their perceptions about the value of the intervention probed with semi-structured one-on-one interviews after completion of the intervention. Results The findings revealed that exposure to the intervention holds benefits for equipping teachers with teaching strategies to create classroom conditions that nurture the development of thinking skills and dispositions that are important for self-regulating, and ultimately self-directing academic and personal wellbeing. Conclusion Cognitive Education is a form of strengths-based education that can play an indispensable role in enabling self-directed academic and personal wellbeing among school learners.